From materials to device design of a thermoelectric fabric for wearable energy harvesters. Issue 24 (2nd June 2017) - Ito, Mitsuhiro; Koizumi, Takuya; Kojima, Hirotaka; Saito, Takeshi; Nakamura, Masakazu
Abstract : We propose a design and fabrication process for fabrics containing thermoelectric generators (TEGs) in the form of carbon nanotube composite threads intended for energy harvesting of low-temperature waste heat. Abstract : We propose a design and fabrication process for fabrics containing thermoelectric generators (TEGs) in the form of carbon nanotube composite threads intended for energy harvesting of low-temperature waste heat. Our prototype thermoelectric fabric with an integrated p/n-stripe-patterned CNT thread shows potential as an easy-to-use power source for wearable electronics.